The Good, the Bad, and the Robust: Climate Change Adaptation Choices for the Port of Rotterdam, Port of San Diego, and Naval Base Kitsap - Bremerton - Smith, Riley W. (My University, 2015)
Due to the inevitability of climate change, long-term adaptation planning is now a necessary facet of infrastructure planning. The projected impacts of sea level rise on coastal infrastructure are particularly dramatic. Although the U.S. Navy has publicly recognized the potential impacts to Navy infrastructure from climate change, adequate guidance has not been provided to assist Navy infrastructure planners with planning for an uncertain future. This thesis provides a comparative analysis of climate change adaptation choices for the Port of Rotterdam, Port of San Diego, and Naval Base Kitsap - Bremerton. Adaptation planning by ports is the focus of this project due to the similarities between the functions and infrastructure of military and commercial ports. The overarching research intent is to analyze the robustness of current adaptation planning for ports, identify robust yet practical planning choices, and construct a functional adaptation planning framework for use by Navy infrastructure planners. This project analyzed six key adaptation choices for the ports from a robustness perspective: climate change scenarios, decision support tools, adaptation strategy, adaptation actions, adaptation funding sources, and adaptation planning timeframe. Each of the ports' adaptation choices was evaluated using a literature-based methodology, the results of which informed recommendations of the most robust planning choices the U.S. Navy could practically make. The comparative study found the most robust yet practical climate scenario is use a series of scenarios as decision thresholds for flexible, adaptive decision-making. The most robust decision support tool is a combination of methods which are tolerant of uncertainty, such as the reasonable person decision path and resilience planning. The recommended adaptation strategy is a combination of protection, accommodation, and rebuild and recover approaches. A complete list of recommended adaptation actions is location-dependent, though certain actions are robust regardless of location and rate and extent of climate change. Practical, robust recommendations for adaptation planning timelines and financing are 2100 and multiple types of federal funding, respectively. Overall, a planning framework based upon the robustness of adaptation choices made for ports is a promising approach to climate change adaptation planning.
Thesis (Master's)--University of Washington, 2015
Keywords: adaptation planning; climate change adaptation; decision making; infrastructure; robust; urban planning; Urban planning; Climate change; urban planning